Implementasi Tingkat Nasional dan Daerah atas Konsensus ASEAN 2017 dalam Perlindungan Pekerja Migran Indonesia - Sudagung, Adityo Darmawan; Olifiani, Laras Putri (Universitas Diponegoro, 2020)
This paper seeks to explain the implementation of the ASEAN Consensus 2017 on the issue of migrant workers’ protection. Entikong was chosen as a research object because of its position as Indonesia’s border gate that distributes migrant workers to Malaysia. The problem of migrant workers still an obstacle to ASEAN member states. The consensus brings a new hope towards a better protection on the issue of migrant workers. Nevertheless, Indonesia has been struggling with the cases of migrant workers. This paper employs the concept of multilevel governance and human security. We argue that at the national and local level, the implementation was quite good. There were some different understandings regarding the consensus. Local government or vertical institution in the region was not well informed about the document, but their acts on the issue of migrant workers were implementing the spirit of the consensus. On the international level, Indonesia also participated in conducting an action plan on the implementation of ASEAN Consensus and promoted other ASEAN members to create a legally binding instrument on the issue of migrant workers protection in Southeast Asia.